The Hollerroute – landscape awareness as a driving factor in regional development - Kruse, Alexandra; Paulowitz, Bernd (TÁJÖKOLÓGIAI LAPOK, 2019)
The Holler Landscapes are a European testimony of a marsh and dyke landscape through land reclamation starting in the High Middle Ages. This Dutch originating cope cultivation were found in many places in Europe, but spread particularly in Germany and Poland. These landscapes had, and for most of their part still have in common that they were created by Dutch water experts – most often on demand from local authorities, like archbishops or kings – and are therefore called Holler Colonies. The tangible landscape heritage was often linked to the import of many Dutch society features (e.g. related to laws, habits, equal rights of men and women), making the Holler Colonies a unique document to the intangible heritage as well. Today, the remainders of these landscapes give an important testimony to European economic and social history. These landscapes were predominately shaped during the great clearances in the High Middle Ages, with some of them, in particular Poland, dating from a later period. Of course, not all landscapes and associated traditions have survived until today. Several Holler landscapes have been completely transformed by more recent land reclamation processes or due to abandonment. The examples that still bear the vivid impression of the land transformation are therefore not only a unique but as well rare testimony of tangible and intangible heritage of European history. The article focusses on an awareness raising process that took place in the Altes Land (Lower Saxony, Germany) within the last 15 years: After a difficult beginning, finally the understanding of the historical transformations and of the particularity of this traditional cultural landscape became a trigger towards local and regional development strategies. The awareness on the Dutch landscape heritage lead to an identification process among the inhabitants and last but not least, triggered local development. It helped finally to start the will to sustain the historic regional character, allowing a sustainable economic development, and is accompanied by tourism and awareness building measures. One of them is the “Holler Route” – a project recognized within the European Year of Cultural Heritage, which will develop, among others, teaching materials about Holler Landscapes which will be integrated into the official geography curriculum for schools and will be available at the online-education server (NibiS) of the Federal State of Lower Saxonia.